2023
DOI: 10.3389/fendo.2022.997880
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the microenvironment of diabetic foot ulcers and potential drug identification based on scRNA-seq

Abstract: BackgroundDiabetes foot ulcers (DFUs) are a type of foot infection, ulcer, and/or deep tissue destruction caused by neuropathy and vascular disease in the distal extremities of diabetic patients. Its pathogenesis and its microenvironment are not entirely understood.MethodsInitially, the GSE165816 data set from the GEO database was utilized for single cell analysis to reveal the microenvironment and functional status of DFUs. The GSE199939 RNA-seq data set was utilized for external validation. On the basis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…However, other cell types, such as immune cells, endothelial cells, and fibroblasts, play an important role in the wound-healing process. They could be potential druggable targets with further paired, cell-specific refined transcriptomic data 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…However, other cell types, such as immune cells, endothelial cells, and fibroblasts, play an important role in the wound-healing process. They could be potential druggable targets with further paired, cell-specific refined transcriptomic data 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Through a cluster analysis of the data from the GEO database, Li et al [ 7 ] and Wang et al [ 8 ] found that the proportions of macrophages, leukocytes and monocytes were higher in patients with DFUs, which indicated a higher level of inflammation; also, the elevated proportions of pluripotent stem cells and stromal cells were observed in patients with DM, which indicated a higher level of dryness. These findings were in line with research by Theocharidis et al [ 9 ], who noted that DFU healers had a higher presence of naive and early differentiated progenitor T-lymphocytes, while non-healers had more cytotoxic natural killer T cells at the systemic level.…”
Section: Single-cell Sequencing In Diabetic Wound Healingmentioning
confidence: 99%
“…The biomaterials selected for developing wound dressing can simply shift the wound-healing cascade. 9 The development of bioactive wound dressings is useful for changing the local wound environment. The controlled delivery of bioactive molecules plays a significant role in the wound-healing process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The development of wound-specific dressing materials is a safe and cost-effective approach for diabetic wound management. The biomaterials selected for developing wound dressing can simply shift the wound-healing cascade . The development of bioactive wound dressings is useful for changing the local wound environment.…”
Section: Introductionmentioning
confidence: 99%